LEGAL BASIS FOR MATERNITY BENEFITS FOR WOMEN WORKING IN THE PRIVATE SECTOR UNDER STATE SOCIAL INSURANCE PRACTICAL ISSUES AND LEGISLATIVE IMPROVEMENT PROPOSALS - qizi, Adolat Settiyeva Faxriddin (PT ANTIS International Publisher, 2024)
This article discusses the organization of maternity benefits for women working in the private sector in Uzbekistan under state social insurance. It highlights the issues that arise in practice and the existing challenges in the current system. The focus is on the practical problems faced during the payment of maternity benefits to women employees working in the private sector, i.e., outside state-funded organizations, based on employment contracts with entrepreneurial entities. The article also provides legal and theoretical proposals to address these issues. Based on the research conducted, scientific and theoretical suggestions for improving the sector in the future are offered.